Behavioural risk factors for cardiovascular diseases among adolescents of secondary school in Tulsipur Sub-Metropolitan City, Nepal: A cross-sectional study - Sita Bista; Bishow Puri; Sanju Maharjan; Poshan Thapa; Buna Bhandari (PLoS ONE, 2025)
Background Cardiovascular diseases (CVDs) are a leading cause of global death and disability, affecting one-third of adult population. Often overlooked in school-going adolescents, behavioural risk factors are crucial contributors to CVD risk which begin early and accelerate during adolescent period. This study aims to assess the behavioural risk factors and their associated determinants among adolescents of Tulsipur Sub-Metropolitan City, Nepal. Methods A school-based cross-sectional study was conducted among 361 adolescents aged 16–19 years studying in grade 11 and 12 from public and private schools. Schools were selected using a stratified proportionate sampling method. Data were collected through a self-administered, structured, and validated questionnaire covering socio-demographic characteristics, behavioural risk factors of CVDs, and parental information. Descriptive and analytical statistics were used to analyse the data. Results The most prevalent behavioural risk factor was the consumption of calorie drinks (99%), followed by sedentary behaviour (60%), insufficient fruit and vegetable intake (57%), physical inactivity (35%), and consumption of processed food high in salt (33%). The prevalence of current smoking, alcohol consumption, and smokeless tobacco use was 12%, 10%, and 9% respectively. Key factors associated with the behavioural risk include maternal education, ethnicity, and education system. Parental tobacco and alcohol use were also associated with adolescent smoking and alcohol consumption. Conclusions The high prevalence of CVD risk factors among adolescents in Nepal highlights the urgent need for targeted interventions in both household and school settings. These interventions should aim to reduce behavioural risk factors to prevent the future burden of CVDs in resource-limited areas like Nepal.